Consensus on the diagnosis, treatment and follow-up of patients with age-related macular degeneration eligible for ranibizumab. (June 2012) - Pece, Alfredo; Azzolini, Claudio; Parodi, Maurizio Battaglia; Bottoni, Ferdinando; Danzi, Paola; Donati, Simone; Introini, Ugo; Pucci, Vincenzo; Semeraro, Francesco; Viola, Francesco
Age-related macular degeneration (AMD) is an irreversible pathology that is the principal cause of serious loss of central vision and legal blindness among people over 60 years of age. There are two forms of AMD: the dry, or atrophic form, and the wet, neovascular form. The latter is less frequent but is the cause of approximately 80–90% of cases of serious loss of vision in a short time period. Early diagnosis is therefore essential to permit intervention as promptly as possible. Currently, the most effective therapy for neovascular AMD uses the new class of anti-VEGF drugs, and ranibizumab is today's 'gold standard' for this treatment. The Progetto LUCE (LUCE Project) consists of an advisory board of retinal disease specialists in Lombardy, Italy, whose task is to propose a consensus for the diagnosis, treatment and follow-up of neovascular AMD patients treated with ranibizumab on the basis of a review of the scientific evidence and Italian national health service regulations and the clinical experience of the advisory board members.